Potret Penelitian Atlet Olahraga oleh Akademisi Indonesia: Studi Bibliometrik Berbasis Scopus - Kuston Sultoni; Jajat Jajat; Adang Suherman (Universitas Galuh, 2026)
ABSTRACTResearch on sports athletes by Indonesian scholars has grown rapidly, yet a comprehensive understanding of its patterns and directions remains limited. This study aims to map the research landscape using a Scopus-based bibliometric approach. Data were retrieved using the keyword “athlete” in the title, abstract, and keywords with Indonesian affiliations for the period 2010–2026, yielding 1,532 publications. The analysis covered publication trends, source journals, authors, affiliations, document types, and subject areas. The results show a significant increase in publications, particularly after 2018, with journal articles dominating (80.1%) and a concentration in journals such as Retos and International Journal of Human Movement and Sports Sciences. Research contributions are largely dominated by a limited number of authors and institutions, focusing mainly on health professions (27.2%) and medicine (25.0%). Despite rapid growth, gaps remain in contribution distribution, publication quality, and multidisciplinary integration. This study provides a comprehensive overview and a strategic basis for advancing more impactful and globally competitive sports science research. Keywords: Bibliometric analysis, sports athletes, Indonesian scholars, Scopus, research trends ABSTRAKPenelitian tentang atlet olahraga oleh akademisi Indonesia menunjukkan perkembangan yang pesat, namun pemahaman komprehensif mengenai pola dan arah riset masih terbatas. Penelitian ini bertujuan memetakan lanskap penelitian tersebut melalui analisis bibliometrik berbasis Scopus. Data diperoleh menggunakan kata kunci “athlete” pada judul, abstrak, dan kata kunci dengan afiliasi Indonesia pada periode 2010–2026, menghasilkan 1.532 publikasi. Analisis dilakukan terhadap tren publikasi, sumber jurnal, penulis, afiliasi, jenis dokumen, dan bidang subjek. Hasil menunjukkan peningkatan signifikan publikasi terutama setelah 2018, dengan dominasi artikel jurnal (80,1%) dan konsentrasi pada beberapa jurnal seperti Retos dan International Journal of Human Movement and Sports Sciences. Kontribusi penelitian masih didominasi oleh sejumlah kecil peneliti dan institusi, serta berfokus pada bidang health professions (27,2%) dan medicine (25,0%). Meskipun pertumbuhan pesat terjadi, masih terdapat kesenjangan dalam distribusi kontribusi, kualitas publikasi, dan integrasi multidisiplin. Studi ini memberikan gambaran komprehensif sekaligus dasar strategis untuk pengembangan riset keolahragaan yang lebih berkualitas dan berdaya saing global. Kata Kunci: Analisis bibliometrik, atlet olahraga, akademisi Indonesia, Scopus, tren penelitian